2017
DOI: 10.1016/j.jenvman.2016.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Wheat bran valorisation: Towards photocatalytic nanomaterials for benzyl alcohol photo-oxidation

Abstract: a b s t r a c tIn this work, we have successfully synthesized a set of titania photocatalytic nanocomposites by the incorporation of different TiO 2 content on wheat bran residues. The obtained catalysts were characterized by different techniques including UVeVis spectroscopy, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and Transmission Electron Microscopy (TEM) while their photocatalytic activity was investigated in the oxidation of benzyl alcohol under UV light irradiation. Benzaldehyde y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In addition, the presence of the residue in the structure for modulating the optical and chemical properties of the final catalysts has been also studied. In particular, a notable improvement of the selectivity to benzaldehyde from benzyl alcohol was detected for samples in with titania was modified with wheat bran residues . Electronic wastes are also an interesting source to obtain photocatalysts .…”
Section: Environmental Photocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the presence of the residue in the structure for modulating the optical and chemical properties of the final catalysts has been also studied. In particular, a notable improvement of the selectivity to benzaldehyde from benzyl alcohol was detected for samples in with titania was modified with wheat bran residues . Electronic wastes are also an interesting source to obtain photocatalysts .…”
Section: Environmental Photocatalysismentioning
confidence: 99%
“…[172] Electronic wastes are also an interesting source to obtain photocatalysts. [173][174][175] In a representative example, a nano-Cu 2 O/TiO 2 photocatalyst from waste printed circuit boards was obtained by electrokinetic process. [174] There is a lot of waste potentially useful for obtaining this kind of material.…”
Section: Photocatalytic Materialsmentioning
confidence: 99%
“…According to the 1500 results of the study, the extraction yield was found to increase by increasing the particle size and 1501 temperature. In a study by Ouyang et al [288] a set of titania nanocomposites have been prepared 1502 by the incorporation of different TiO2 content on wheat bran residues. The photocatalytic activity of the prepared titania nanocomposites was investigated in the oxidation of benzyl alcohol under UV light irradiation.…”
Section: Other Types Of Biomass Sources Upcyclingmentioning
confidence: 99%
“…Recent works from our group show our dedication in upgrading biomass/waste/by-products to carbonaceous systems for catalytic purposes in a variety of reactions. Ouyang et al [104] have synthesized photocatalytically active wheat bran@TiO2 via mechanochemical activation. In particular, 10% Ti-Bran yielded 22% of benzaldehyde at 33% conversion of benzyl alcohol, comparable to commercial TiO2.…”
Section: Biomass Conversion For Catalytic Materialsmentioning
confidence: 99%